A variable structure-based algorithm for adaptive cruise control - Doria-Cerezo, Arnau; Olm, Josep M.; Benedito, Ernest; Biel, Domingo (2018 15th International Workshop on Variable Structure Systems (VSS), 2018)
This paper presents an Adaptive Cruise Control algorithm for vehicles based on a variable structure systems approach. The main feature of the proposed design is that the two driving modes, namely distance and speed regulation, are met enforcing sliding modes and asymptotic tracking, respectively. This is achieved using an intervehicle, distance-dependent switching surface able to induce sliding motion when the aimed cruise velocity of the target vehicle is higher than that of the preceding vehicle, and to asymptotically track such cruise velocity when it is lower or equal than the velocity of the preceding vehicle. The algorithm is validated through numerical simulations.